Introductory Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-805-X
ISBN 13: 978-0-13417-805-9

Chapter 5 - Section 5.4 - Polynomials in Several Variables - Exercise Set: 4

Answer

$-16$

Work Step by Step

Substituting $x=2$ and $y=-3$, the given expression, $ x^3y-xy+2 ,$ evaluates to \begin{array}{l}\require{cancel} (2)^3(-3)-(2)(-3)+2 \\\\= (8)(-3)-(-6)+2 \\\\= -24+6+2 \\\\= -18+2 \\\\= -16 .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.